An Investigation of First-Year Students' and Lecturers' Expectations of University Education - Hassel, Stefanie; Ridout, Nathan (Frontiers in Psychology, 2018)
Transition from school to university can cause concern for many students. One issue is the gap between students’ prior expectations and the realities of university life, which can cause significant distress, poor academic performance and increased drop-out rates if not managed effectively. Research has shown several similarities in the expectations of staff and students in regards to which factors determine academic success, but there is also evidence of dissonance. For example, staff consider independent study and critical evaluation as key factors, whereas students view feedback on drafts of work and support from staff as being most important. The aim of the current study was to determine what expectations students hold when starting university education, and what expectations university lecturers have of students entering university. Lecturers (n=20) and first year students (n=77) completed a series of questionnaires concerning their expectations of learning in HE (staff and students) and their approach to teaching (staff). Results revealed that students have largely realistic expectations of university. For example, the majority expected to be in charge of their own study. Some unrealistic expectations were also evident, e.g., most expected that teaching would be the same at university as it had been at school. The expectation that lecturers would provide detailed notes varied as a function of student age. Lecturers reported modifying their expectations of students and adapting their teaching approach according to year of study. Information-transmission/teacher-focused style was more common when teaching 1st year students; a more concept-changing/student-focused approach tended to be used when teaching 2nd year students (and above). Lecturer’s expectations of student engagement did not differ according to year. Less experienced lecturers reported more negative expectations of student engagement than did experienced lecturers. In line with previous work, we observed overlap in expectations of staff and students, but some clear differences too.